Pentingnya Pemahaman Pancasila di Era Millenial - Rizki, Ekfandiantowo Nur (Jurnal Pendidikan Kewarganegaraan Undiksha, 2024)
This paper is motivated by the weakening internalization of Pancasila values within society, particularly among millennials, amid rapid advances in science and technology and a shift toward more individualistic life orientations. It aims to rearticulate ways of applying Pancasila so that it remains relevant to today’s social–digital ecosystem. The study employs a literature review and descriptive–qualitative analysis of everyday practices in offline and online spaces, complemented by examples of community initiatives. Findings indicate an erosion in the internalization of mutual cooperation (gotong royong), deliberation and consensus (musyawarah), and social justice, reflected in egocentric interaction preferences and lower collective participation; however, pockets of positive practice—discussion forums, hobby communities, and digital collaborations—reveal potential pathways for revitalization. The study concludes that re-actualizing Pancasila requires contextual approaches: youth-friendly language, meaningful participatory spaces, and role modeling from micro to institutional levels. Practical implications include strengthening project-based character education and service-learning, integrating critical digital literacy into curricula, fostering government–school–community/edtech partnerships for collaborative programs, and running evidence-informed positive-narrative campaigns tracked through indicators of social participation and community cohesion..